A Study of Substance Use Among Male Drug Addicts in Iran - Esmat Fazeli (Drug Control Headquarters, Research and Education Office, 2002)
The present investingation was designed to explore the extent to which the elements of the Health Belief Model (HBM)predict substance use among male drug addicts in Iran. A self - report research instrument (questionnaire)was developed and administered to obtain data. One hundred and twenty four subjects voluntarily participated in the survey . The contributers had already attended places like Health Organization and other detoxicating centers in order to stop their risky behaviour . There were four distinct predictive components (perceived susceptibilty, perceived severity, perceived benefits and perceived barriers)in the HBM. These components were internally consistent and together examined the risky behaviour, substance use. This study revealed that the model is reliable, valid, robust and feasible for examining substance use behavioure. The theoretical components of the HBM appeared to have different predictive ability perceived benefits showed the strongest power . This is consistent with a great number of research findings in this area. In contrary , predictive ability of predictive power of preceived sevirity . declined - all research hypothses were approved except predictive power of percieved sevirity. Rationale for this decline refres to the repetition of relapse after detoxication .In fact, " believing in serverity for the consequences of a risky behaviour pales through repetition of the behavioure ".